If you want to change the world you have to start with yourself: The impact of staff reflective practice within the Offender Personality Disorder pathway. (September 2020) - Webster, Nicole; Doggett, Laura; Gardner, Stephanie
The offender personality disorder (OPD) pathway was implemented in 2012 to help improve services for people with personality difficulties within the criminal justice system. The OPD pathway acknowledges the importance of supervision, training and reflective practice for staff working with this client group and such activities have therefore been embedded within this initiative. Despite the research from this pathway identifying benefits to both staff and service users, there is a gap in knowledge about the impact of reflective practice. This study aims, therefore, to increase this knowledge base by exploring staff's experience and perception of reflective practice as part of the OPD pathway programme. Focus groups and semi-structured interviews were completed with 32 members of National Health Service and National Probation Service staff within offender management teams and approved premises in the North East of England. Thematic analysis was used to analyse the data, resulting in the emergence of four key themes relating to the utility of reflective practice sessions. The findings suggest that reflective practice is useful, however, there are some barriers to attending sessions. The findings have implications for service delivery and workforce development within the OPD pathway programme and more widely within NPS.